2021
DOI: 10.5114/ceh.2021.104676
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of immunohistochemical staining of bile tracts in biliary atresia

Abstract: Aim of the study:To assess ductular proliferation (DP) and ductal plate malformation (DPM) in biliary atresia (BA) by means of immunohistochemical staining using cytokeratins CK7 and CK19 and neural cell adhesion molecule (NCAM) antibody CD56. Material and methods: In 10 cases of BA, liver surgical biopsies obtained at the time of hepatoportoenterostomy were stained with H&E, PAS, Gomori and Azan methods. Immunohistochemical technique was used to outline bile ducts, ductular reaction, reactive bile duct/ductul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Among these patients, 62.8% had positive expression of CK7, 70% had positive expression of CK19, and 57% had no expression of HepBar-1, which supports the findings of another study ( 10 ) and may be an important feature in diagnosis. High expression of CK7 and CK19 suggests that the origin of the tumor could be from the biliary epithelium ( 11 ). Other less common markers that were reported in the literature include CK8, CK18, CK20, IDH1, LMP1, CEA, AFP, CDX2, CA-199, HER-2, TTF-1, and MNF116 ( Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Among these patients, 62.8% had positive expression of CK7, 70% had positive expression of CK19, and 57% had no expression of HepBar-1, which supports the findings of another study ( 10 ) and may be an important feature in diagnosis. High expression of CK7 and CK19 suggests that the origin of the tumor could be from the biliary epithelium ( 11 ). Other less common markers that were reported in the literature include CK8, CK18, CK20, IDH1, LMP1, CEA, AFP, CDX2, CA-199, HER-2, TTF-1, and MNF116 ( Supplementary Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biliary atresia is a common cause of pathological jaundice in infants, with complex etiology, and the major pathological changes of BA were collagen deposition and liver tissue fibrosis, which can eventually lead to death of the child ( Cielecka-Kuszyk et al, 2021 ). Studies have shown that liver fibrosis plays an important role in the course of BA and that the process of liver fibrosis does not stop after Kasai surgery in children with BA ( Zhou et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Azan staining was performed as described previously 28 , for category 1 sections shown in Suppl. Data 1 .…”
Section: Methodsmentioning
confidence: 99%